Hepatogenic differentiation of induced pluripotent stem cells and embryonic stem cells in 3D hydrogel system. - Liao, Yanwan. (2013)
Liver transplantation is the only effective treatment of end-stage liver disease, but it is limited by the sustained shortage of donor organ with the growing demand. Primary hepatocytes may be the first choice for liver regeneration, however, it only has finite source and rapidly loses phenotype when cultured in vitro, leading to few clinical usage. Another option is the embryonic stem cell (ESC), which also gets obstructed by immune rejection and ethical issues. Induced pluripotent stem cell (iPSC) that derives from autologous somatic cells has similar ability to ESC, so it can be a competitive alternative cell source to generate liver tissue. Previous studies in 2D and 3D in vitro cultures have proved the ability of iPSCs to differentiate into liver cell lineages.